Effect of Canola Oil on Cholesterol and Fatty Acid Composition of Egg-yolk of Laying Hens - Rowghani, E.; Arab, M.; Nazifi, S.; Bakhtiari, Z. (International Journal of Poultry Science, 2007)
This experiment was conducted to determine the effect of a dietary Calcium Soap of Fatty Acids (CSFA) and canola oil on cholesterol and omega-3 fatty acids content of the egg. A total of 120 Hy-line white layer (24-week old) were randomly divided into four experimental treatments with six replicates (5 hens per cage) and arranged in a completely randomized design. The experimental period lasted eight weeks and during this period, the birds had free access to feed and water. Experimental diets consisted of: 1) basal diet; 2) basal diet with 1% calcium soap of fatty acids; 3) basal diet with 3% canola oil and 4) basal diet with 5% canola oil. Egg weight, egg-yolk and egg white weights, yolk and egg cholesterol concentrations, linolenic and docosahexaenoic acids (DHA) content of the yolk were measured. Egg and egg white weights were not significantly different (p>0.05) among treatments. Adding 3% canola oil and 1% CSFA had no significant effect on egg-yolk weight, but addition of 5% canola oil showed significant effect on egg-yolk weight (p< 0.05). CSFA had no significant effect on egg and yolk cholesterol, linolenic acid and omega-3 concentrations (p>0.05). Canola oil at 3 and 5% increased the percentage of linolenic acid by 2.7 to 4.73 folds to give levels of 3.43 and 6.02 percent of total fatty acids, respectively. Canola oil increased DHA content of the egg (p< 0.05). By adding 3 and 5% canola oil, the percentage of DHA increased by 8.73 and 9.8 folds compared with the control diet, respectively. Canola oil at 3 and 5% increased percentage of total omega-3 fatty acids by 3.3 and 4.75 folds (4.72 vs 6.80%) as compared with the control diet (1.43%). Based on the results it seems that adding 5% canola oil to the laying hen diet based on corn and soybean meal, can increase omega-3 fatty acids content of egg-yolk which may have beneficial roles on human health.